Children’s Open Community Center, Valparaíso, Chile, 2022 - Lautaro Ojeda; Andrea Pino (ARQ, 2023)
Design usually starts with an idea. In this project, it begins with a question about the tools to generate a dialogue between the community, designers, academia, and authorities. The resulting project creates a public space where there wasn’t one, utilizing the slope to increase recreational areas and guarantee the accessibility and permeability of the block.